SISTEM INFORMASI SURAT PERINTAH PERJALANAN DINAS DI DINAS PPKBP3A KABUPATEN KAMPAR - Rifael, Dandy Aditya; Marwa, Safni; Azriadi, Emon (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
The Department of Population Control, Family Planning, Women Empowerment, and Child Protection (PPKBP3A) of Kampar Regency faces challenges in managing Official Travel Order Letters (SPPD) due to the manual nature of the current process. This manual system has led to several issues, such as lengthy processing times, unintegrated approval flows, delays and errors in reporting, as well as difficulties in document storage and retrieval. This study aims to design and develop a web-based Official Travel Order Information System (SPPD) to enhance the efficiency of official travel management within the department. The system was developed using the Waterfall model, which includes sequential stages of analysis, design, implementation, and testing. The development process utilized the Laravel framework and PHP programming language. To ensure that all features function as expected by users, the system was tested using the Black Box Testing method. The result of this research is a functional information system that successfully passed the functional testing and is capable of simplifying the submission, creation, approval, and archiving processes of SPPD. The implementation of this system is expected to improve work efficiency, speed up administrative processes, and reduce errors and reliance on manual procedures at the PPKBP3A Office of Kampar Regency.